Modelling safety critical systems with ageing components, with application to underground railway risk and hazards - Naybour, Susannah (2021)
In this thesis methodologies for modelling risk on ageing systems are developed. In the first stages of the thesis, two systems on an underground railway are used to demonstrate the modelling approach. In the latter stages of this thesis the modelling approach is expanded further, presenting a method for optimisation of a phased maintenance strategy, an inclusion of uncertainty in model outputs and an approach to model size reduction.